2016
DOI: 10.18632/oncotarget.13854
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of NF-YA splicing isoforms and Lamin A status in low grade endometrial cancer

Abstract: Although most cases of low grade (G1) endometrial cancer (EC) do not behave aggressively, in rare instances, can progress in a highly aggressive manner. In this study we analyzed formalin-fixed, paraffin-embedded (FFPE) EC tissues to find novel clinical and biological features to help diagnosis and treatment of G1 ECs s in order to better stratify patient risk of recurrence. A retrospective cohort of FFPE specimens from patients with EC (n=87) and benign tissue specimens (NE) from patients who underwent a hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Western blotting. IL-16 protein level was analyzed by western blotting assay according a previous study (13,15). Proteins were extracted in cell lysis buffer (89900; Thermo Fisher Scientific, Inc.) on ice followed by centrifugation at 12,000 x g for 10 min at 4˚C, then boiled at 100˚C for 10 min.…”
Section: Rna Extraction and Reverse Transcription-quantitative Polymementioning
confidence: 99%
“…Western blotting. IL-16 protein level was analyzed by western blotting assay according a previous study (13,15). Proteins were extracted in cell lysis buffer (89900; Thermo Fisher Scientific, Inc.) on ice followed by centrifugation at 12,000 x g for 10 min at 4˚C, then boiled at 100˚C for 10 min.…”
Section: Rna Extraction and Reverse Transcription-quantitative Polymementioning
confidence: 99%
“…In endometrial tissues, the exclusive presence of NF-YAl observed in benign samples suggested that it may represent a marker of differentiation, in opposition to NF-YAs, which is expressed into cancer tissues and linked to poorly differentiated cells [26]. In breast and lung cancers, the ratio Cells 2020, 9, 760 4 of 28 between NF-YAl/NF-YAs isoforms is dramatically shifted towards NF-YAs [27,28].…”
Section: Nuclear Transcription Factor Y (Nf-y)mentioning
confidence: 99%
“…MDA-MB-231) undergone epithelial-mesenchymal transition (EMT) usually contain soer nuclei. [52][53][54] Hence the nal modulus E f and modulus jump DE could provide the insightful information of the physical distortion (either stiffening or enlarging) of the nuclei.…”
Section: Cell Classication Based On Cell Physical Properties Of Largmentioning
confidence: 99%